Identification of audio and room parameters for optimum speech intelligibility in room - Ng, Tsing Chun (2007)
The installation of electronic amplification system in the meeting or conference room is intended to having a louder, clear and an even sound propagation. Furthermore the conversation exchanged will be at ease, since speakers do not have to raise their voice to be heard. However, the interaction between amplified sound waves in the room and the characteristics of the room may not produce desirable results, which is clarity of the speech. The aim of this project is to identify room and audio parameters in meeting room, which influence conversation so that optimum speech intelligibility can be achieved in that room. The room and audio parameters such as room shape and size, room furnishes, reverberation time and background noise, these characteristics will be studied so as to evaluate their effects on speech intelligibility. CARA program is used to simulate room samples to determine which acoustic design can achieve the optimum speech intelligibility. From the simulation results it is found that 17 out of 18 of the room design model within the range of acceptable speech intelligibility. The proper selection of acoustical materials for the surfaces of ceiling, wall and floor in these meeting room models provide optimum acoustical properties and meet the design requirements.